Developing Students’ Productive Skills Through Problem Based and Project Based Learning Environmental Models - Siti Oriza Salsijanti (Lembaga Penelitian dan Pengabdian Masyarakat STI. Blambangan Banyuwangi, 2023)
It is found that most of the students in Senior high school do not have adequate awareness of the environment and also find writing difficult. They are also not able to communicate correctly in English. To overcome these problems, some learning models were used to teach environmental education as a tool to construct their knowledge. The study investigated and integrated environmental education into the PBL and PJBL methods of learning English. Quasi-experimental design, non-randomized control group, and pretests and posttests were used in the study. The subjects of the study were taken from the population of the XI grade students of SMAN 1 Gambiran, Banyuwangi, Indonesia in 2021/2022. The result of the Mann-Whitney U-Test can be shown that students taught using PBL and PjBL through scaffolds and a campaign achieve significantly higher scores in writing and speaking compared to those taught using the conventional method.